1035325 Efektivitas Abdominal Stretching Exercise dalam Menurunkan Intensitas Nyeri Haid (Dismenore) - Ratu Nirmala Wahyunindita (STIKes Budi Mulia Sriwijaya, 2019)
ABSTRACT Dysmenorrhea is an uncomfortable feeling that arises especially in the first days until the end of menstruation. Dysmenorrhea can affect 50% of women causing the inability to carry out daily activities dor 1 to 3 days during menstruation. Pain that can be experienced can be sharp, deep, dull cramps and pain located in the suprapuis area. The most commonly used pharmacological therapy for cases of menstrual pain is with Non-steroidal antiinflammatory drugs (NSAIDs). Other way to relief dysmenorrhea with minimal side effects is stretching. Stretching is known to reduce the frequency and intensity of dysmenorrhea. Abdominal stretching exercise are recommended for adolescent to reduce severity of dysmenorrhea. Keywords: Abdominal stretching exercise, remaja, dismenore